Statistical Modeling of Multivariate Reliability Function Using Copula Method in the Presence of Censoring - R. Muradov; A. Abdushukurov (Karshi Multidisciplinary International Scientific Journal, 2024)
Numerous scientific and practical researches conducted around the world aremostly focused use on the methods of statistical modeling. Statistical models play an important role in various fields. Examples include mathematical models in the physics, astronomy, biology, medicine, economics, demography, sociology, psychology, marketing, political science, engineering sciences, machine learning, computer science, natural sciences and other related fields. In this article, we investigate the problem of statistical modeling of multivariate reliability functions. In this case, an algorithm for constructing a statistical model is developed and the copula method is used in the presence of censoring.